2005
DOI: 10.1007/s11136-004-2657-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing quality of life in eating disorder patients

Abstract: Objective: To examine quality of life among subgroups of eating disorder patients. Method: Self-report questionnaires which included two quality of life measures were completed by 87 individuals referred for treatment to the Australian Capital Territory Eating Disorders Day Program. Health-related quality of life, as measured by the Medical Outcomes Study 12-item Short Form Mental Component Summary scale, and subjective quality of life, as measured by subscales of the World Health Organization Brief Quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
165
0
21

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(193 citation statements)
references
References 37 publications
(35 reference statements)
7
165
0
21
Order By: Relevance
“…This may seem surprising and differs from some previous research showing substantial impairments in QOL among eating disordered women. However, the present results are also similar to prior findings of unexpectedly high reported QOL with AN patients (Mond, Hay, Rodgers, Owen, & Beumont, 2005;Padierna, Quintana, Arostegui, Gonzalez, & Horcajo, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…This may seem surprising and differs from some previous research showing substantial impairments in QOL among eating disordered women. However, the present results are also similar to prior findings of unexpectedly high reported QOL with AN patients (Mond, Hay, Rodgers, Owen, & Beumont, 2005;Padierna, Quintana, Arostegui, Gonzalez, & Horcajo, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…Del mismo modo, Mond et al 42 al usar la versión abreviada de The World Health Organization Quality of Life Assessment Instrument (WHOQoL-BREF) y el SF-12, entre grupos de pacientes con desórdenes alimentarios, encontraron que tomados juntos mostraban un marcado empeoramiento en lo referente a la CV relacionada a la salud y la CV subjetiva relacionada con el grupo control. Sin embargo, en nuestro estudio no son sujetos quienes tienen un diagnóstico, sino que auto reportan una conducta.…”
Section: Grupos/calidad De Vidaunclassified
“…[1][2][3][4][5][6][7][8][9][10] Padierna et al 6 showed that after 2 years of treatment and follow-up, ED patients were still more dysfunctional in all areas of life than women of the general population although their perception of their QOL had improved. De la Rie et al 1 also showed that ED patients, even after symptoms are no longer manifest, still report a poorer QOL than a normal reference group.…”
Section: Introductionmentioning
confidence: 99%
“…The QOL for EDs in most of these studies was assessed using general health-related QOL measures, such as the Short Form-36 (SF-36) [1][2][3][4][5][6][7][8] or the Nottingham Health Profile. 9 Although the use of a generic health-related QOL measure helps to provide insight into the QOL of a patient group in comparison to other patient groups or a normal reference group, it has several limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation